Impact of talker variability on L2 word recognition among Japanese EFL learners - Noriko Matsuda (Vocabulary Learning and Instruction)
This article is a pilot study investigating auditory word priming in 40 Japanese learners of English using speeded repetition tasks to measure the impact of talker changes on second language (L2) word recognition. The results showed that by focusing more on the perceptual dimension, in single-talker conditions, word recognition time was statistically significantly shorter and a perceptual learning effect was seen. However, with talker changes, word recognition time significantly increased and the repetition effects were nullified. The results indicate that Japanese English as a foreign language (EFL) learners have high sensitivity to individual attributes of speech and seem to need some variations in auditory input for some period of time without any need for comprehension in order to form robust representations of L2 words.